If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -30)(3x + 3) + -1(2x + -1) * 2 = 0 Reorder the terms: (-30 + 3x)(3x + 3) + -1(2x + -1) * 2 = 0 Reorder the terms: (-30 + 3x)(3 + 3x) + -1(2x + -1) * 2 = 0 Multiply (-30 + 3x) * (3 + 3x) (-30(3 + 3x) + 3x * (3 + 3x)) + -1(2x + -1) * 2 = 0 ((3 * -30 + 3x * -30) + 3x * (3 + 3x)) + -1(2x + -1) * 2 = 0 ((-90 + -90x) + 3x * (3 + 3x)) + -1(2x + -1) * 2 = 0 (-90 + -90x + (3 * 3x + 3x * 3x)) + -1(2x + -1) * 2 = 0 (-90 + -90x + (9x + 9x2)) + -1(2x + -1) * 2 = 0 Combine like terms: -90x + 9x = -81x (-90 + -81x + 9x2) + -1(2x + -1) * 2 = 0 Reorder the terms: -90 + -81x + 9x2 + -1(-1 + 2x) * 2 = 0 Reorder the terms for easier multiplication: -90 + -81x + 9x2 + -1 * 2(-1 + 2x) = 0 Multiply -1 * 2 -90 + -81x + 9x2 + -2(-1 + 2x) = 0 -90 + -81x + 9x2 + (-1 * -2 + 2x * -2) = 0 -90 + -81x + 9x2 + (2 + -4x) = 0 Reorder the terms: -90 + 2 + -81x + -4x + 9x2 = 0 Combine like terms: -90 + 2 = -88 -88 + -81x + -4x + 9x2 = 0 Combine like terms: -81x + -4x = -85x -88 + -85x + 9x2 = 0 Solving -88 + -85x + 9x2 = 0 Solving for variable 'x'. Begin completing the square. Divide all terms by 9 the coefficient of the squared term: Divide each side by '9'. -9.777777778 + -9.444444444x + x2 = 0 Move the constant term to the right: Add '9.777777778' to each side of the equation. -9.777777778 + -9.444444444x + 9.777777778 + x2 = 0 + 9.777777778 Reorder the terms: -9.777777778 + 9.777777778 + -9.444444444x + x2 = 0 + 9.777777778 Combine like terms: -9.777777778 + 9.777777778 = 0.000000000 0.000000000 + -9.444444444x + x2 = 0 + 9.777777778 -9.444444444x + x2 = 0 + 9.777777778 Combine like terms: 0 + 9.777777778 = 9.777777778 -9.444444444x + x2 = 9.777777778 The x term is -9.444444444x. Take half its coefficient (-4.722222222). Square it (22.29938271) and add it to both sides. Add '22.29938271' to each side of the equation. -9.444444444x + 22.29938271 + x2 = 9.777777778 + 22.29938271 Reorder the terms: 22.29938271 + -9.444444444x + x2 = 9.777777778 + 22.29938271 Combine like terms: 9.777777778 + 22.29938271 = 32.077160488 22.29938271 + -9.444444444x + x2 = 32.077160488 Factor a perfect square on the left side: (x + -4.722222222)(x + -4.722222222) = 32.077160488 Calculate the square root of the right side: 5.663670231 Break this problem into two subproblems by setting (x + -4.722222222) equal to 5.663670231 and -5.663670231.Subproblem 1
x + -4.722222222 = 5.663670231 Simplifying x + -4.722222222 = 5.663670231 Reorder the terms: -4.722222222 + x = 5.663670231 Solving -4.722222222 + x = 5.663670231 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4.722222222' to each side of the equation. -4.722222222 + 4.722222222 + x = 5.663670231 + 4.722222222 Combine like terms: -4.722222222 + 4.722222222 = 0.000000000 0.000000000 + x = 5.663670231 + 4.722222222 x = 5.663670231 + 4.722222222 Combine like terms: 5.663670231 + 4.722222222 = 10.385892453 x = 10.385892453 Simplifying x = 10.385892453Subproblem 2
x + -4.722222222 = -5.663670231 Simplifying x + -4.722222222 = -5.663670231 Reorder the terms: -4.722222222 + x = -5.663670231 Solving -4.722222222 + x = -5.663670231 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4.722222222' to each side of the equation. -4.722222222 + 4.722222222 + x = -5.663670231 + 4.722222222 Combine like terms: -4.722222222 + 4.722222222 = 0.000000000 0.000000000 + x = -5.663670231 + 4.722222222 x = -5.663670231 + 4.722222222 Combine like terms: -5.663670231 + 4.722222222 = -0.941448009 x = -0.941448009 Simplifying x = -0.941448009Solution
The solution to the problem is based on the solutions from the subproblems. x = {10.385892453, -0.941448009}
| 5x-57-2x= | | X^4-3x^3+x^2-3x+3=0 | | 35/20=n/4 | | 10=-7x-x^2 | | 4x+-5=7x-3 | | -(6v-2x-1)= | | -2-3-1= | | 270=0.5x^2+36x-40 | | 5-4-4= | | (2x+3)(x-6)-(5x+3)(3x+4)= | | 9r^2-5=76 | | ×/5=7.5 | | 4y+12=7y+36 | | 5m+4=3m+16 | | x^2-2x+2y^2=8 | | 100-50/10*5 | | -23=6r+16 | | 8-6-2= | | (3x-30)(3x+3)-(2x-1)=0 | | y^2-26y+45=0 | | 8m+5=5m+15 | | 11-2x=-x-3 | | -23=6r+12 | | 18r+4= | | -23=16r-5 | | 3x^2+2x-x=0 | | 5x+3=37x | | 54=8g+10-4(3g+12) | | 2(2x+40)=180 | | 54=8g+12-4(3g+12) | | 1x+5=10x | | 12-2y=y-6+3y |